COMPARATIVE BEHAVIOR OF MAGNETIC IRON OXIDE NANOPARTICLES (MIONS) VIA MECHANICAL AND CHEMICAL ROUTES - Fajariman, Ilham Dias; Hidayat, Arif; Diantoro, Markus; Laksono, Yoyok Adi Setio; Wulandari, Nurul Putri; Chusna, Nadiya Miftachul; Yuliana, Futri; Saputra, Kormil; Sunaryono, Sunaryono (Indonesian Physical Review, 2025)
This study successfully synthesized Magnetic Iron Oxide Nanoparticles (MIONs) through two different processes, namely mechanical synthesis (MIONs – M) and chemical synthesis (MIONs – N). The synthesized samples were characterized using X-Ray Fluorescence (XRF), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), and Vibrating Sample Magnetometer (VSM) to determine the elemental composition, morphology, structure, and magnetization of the samples. XRF analysis revealed that iron (Fe) dominated both samples, with concentrations reaching 93.91% for MIONs – M and 89.91% for MIONs – N. SEM morphological analysis showed that the MIONs tended to be spherical and experienced agglomeration, with particle size distribution around 120 nm for MIONs – M and 30 nm for MIONs – N. XRD data indicated that both samples exhibited a cubic spinel Fe3O4 phase, consistent with the AMCSD 0000945 model data. Using the refinement method and Debye-Scherrer equation, the crystallite size and density of MIONs – M were found to be larger than MIONs – N. This correlates with VSM data analysis, where the saturation magnetization of MIONs – M (49.51 emu/g) was greater than that of MIONs – N (26.54 emu/g). These results provide important insights into the characteristics of MIONs and their implications for technological and industrial applications.